1996
DOI: 10.1161/01.str.27.8.1274
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Correlates of White Matter Findings on Cranial Magnetic Resonance Imaging of 3301 Elderly People

Abstract: White matter findings were significantly associated with age, silent stroke, hypertension, FEV1, and income. The white matter findings may not be considered benign because they are associated with impaired cognitive and lower extremity function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

65
1,119
24
41

Year Published

1998
1998
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,352 publications
(1,249 citation statements)
references
References 19 publications
65
1,119
24
41
Order By: Relevance
“…In particular, previous studies reported that ventricular volume increases with age [17,26,46], is higher in males [47], is higher in AD subjects compared to MCI subjects, and is higher in MCI subjects compared to controls [14].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In particular, previous studies reported that ventricular volume increases with age [17,26,46], is higher in males [47], is higher in AD subjects compared to MCI subjects, and is higher in MCI subjects compared to controls [14].…”
Section: Discussionmentioning
confidence: 93%
“…However, it is also possible that large ventricles indicate a pre-existing structural vulnerability that hampers the ability of the brain to delay AD-related pathology progression. For example, earlier studies have suggested that larger ventricles are highly correlated with lower white matter integrity, which may in turn indicate the presence of small vessel disease [26]. This issue may be clarified in the future by relating ventricular size to MRI markers related to AD pathology or white matter integrity, such as volumes of medial temporal lobe structures or radiological assessments of white matter grade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although characteristic pathological features of the diabetic brain have yet not been identified, vascular compromise is common in the elderly and is accompanied by damage to white matter pathways [12,45]. Age and hypertension have been the most consistent predictors of WMHs [32,33,46,47], while some other studies have indicated that diabetes increases the risk of WMHs [13,36,48]. The increased WMHs in elderly diabetic patients, presumably accompanied by as yet unidentified clinical variables, may account, at least in part, for diabetic cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Since cognitive effort normally triggers an increase in cerebral blood supply in response to increasing metabolic demands, any reduction in vascular reactivity is likely to induce a decline in mental efficiency. The greatly increased incidence of white matter lesions in adults with hypertension [52,53] could also underlie the decline in mental efficiency, since the presence of white matter lesions is associated with slower performance on psychomotor tasks like the DSST [54,55]. Whether those declines reflect neural changes secondary to demyelination [56] or to the haemodynamic abnormalities associated with white matter lesions [57] remains to be determined.…”
Section: Discussionmentioning
confidence: 99%